Community, Commons, Common Sense - Lijster, Thijs (2022)
As De Angelis, Federici, and others have noted, there are “no commons without community.” The concept of community, however (as, among others, Jean‐Luc Nancy and Roberto Esposito have shown), has a dark history continuing up until today, when extreme right‐wing or even downright fascist appropriations of the concept have understood it as a static and identitarian unity bound to a specific territory or ethnicity. While commons‐scholars try to circumvent this legacy by emphasizing the commons as a “praxis” (Dardot and Laval) or “organizational principle” (De Angelis), they thereby tend to neglect the important cultural and symbolic connotations of the concept of community (which, in part, seem to make right‐wing movements appealing for certain segments of the population). In my article, I want to raise the following question: Do we need a sense of community for a politics of the commons, and, if so, what concept of community should it be? To answer this question, I will refer back to the use of the concept of “common sense” (sensus communis) in Immanuel Kant’s Critique of Judgment. Characteristic of Kant’s use of the term is that it does not refer to an actually existing community, but rather to an imaginary community that is anticipated in our (aesthetic) judgment. Common sense, in other words, involves “acting as if”—with the dual dimensions of acting (i.e., the community is based in praxis) and as if (an imagined, anticipated community bordering between the fictional and the real).